Comparing the diagnostic value of serum oligosaccharide chain (G-test) and alpha-fetoprotein for hepatitis B virus-related liver cancer - Wan, Lijun; Guo, Li; Hu, Youwen; Huang, Hongyan; Zhang, Moran; Xu, Kedong; De, Gejirifu; Zheng, Fengfei; Wu, Zhengqiang; Hu, Chungen; Wen, Zhili (Clinical biochemistry, 2021)
The study compared the diagnostic efficiency of serum oligosaccharide chain (G-test) and alpha-fetoprotein (AFP) for hepatitis B-related hepatocellular carcinoma (HCC). Serum samples from 100 patients (divided into five groups of 20 each, namely the hepatitis, liver cirrhosis, liver cancer, health, and interference groups) who were admitted to the Second Affiliated Hospital of Nanchang University from October 2019 to January 2020 were collected, and the levels of G-test and AFP were determined. The sensitivity and specificity of the two indicators were compared, and the receiver operating characteristic curve of the subjects was drawn to evaluate the diagnostic values of G-test and AFP for HCC. The diagnostic ability of G-test (area under the curve [AUC]: 0.88 ± 0.05) was better than that of AFP (AUC: 0.76 ± 0.05). When G-test and AFP were combined for detection, the AUC was larger than that of either indicator. The G-test was superior to AFP in the differential diagnosis of early HCC and cirrhosis. A combination of the two indicators (AUC: 0.769 ± 0.05) significantly improved the diagnostic rate for early HCC, indicating that G-test and AFP complemented each other. G-test was better than AFP for screening HCC in patients with chronic hepatitis B and cirrhosis. The combination of the two further improved the diagnostic rate of hepatitis B-related liver cancer. The G-test improves the screening rate of early HCC in patients with cirrhosis. Therefore, these markers are of great clinical significance and can improve the sensitivity of HCC detection and reduce missed diagnosis rates.